POPULATION OF PHOSPHATE SOLUBILIZING BACTERIA AND CHARACTERISTICS IN VARIOUS TYPES OF GROWING MEDIA AND ORGANIC FERTILIZER - S. S., Putri; Budiasa, I K. M.; Roni, N. G. K. (Jurnal Peternakan Tropika, 2019)
Phosphate solubilizing bacteria (BPF) is one type of soil microbes that plays an important role in helping supply nutrients in soil, especially phosphorus (P). This study aims to obtain total plate count (TPC) data, population of phosphate solubilizing bacteria, characteristics of acidity (pH) and temperature on various types of planting media and organic fertilizers. The design used was a completely randomized design consisting of seven treatments, namely: soil (M1), cow manure (M2) slurry (M3), bio-slurry (M4), soil fertilized with cow manure (M5), soil fertilized with slurry (M6), soil fertilized with bio-slurry (M7). The treatments were repeated three times so that there were 21 experimental units. The variables observed in this study were total plate count (TPC), phosphate solubilizing bacteria (BPF), acidity (pH), and temperature.  The data obtained from this study were using analyzed variance analysis, if there were significant differences (P <0.05) then the analysis continued with Duncan's multiple range test. The results showed that the TPC obtained results ranged from 9.40 × 10 7 - 1.84 × 10 9 cfu / g, BPF obtained results ranged 7.23 × 10 6 - 1.77 × 10 8 cfu / g. The highest of acidity (pH) in the M5 treatment is 7.00. The highest temperature in the treatment of M3 and M4 is 31,00 0 C. Based on the results of the study  concluded that the mostopulation of the total plate count (TPC) and population of phosphate solubilizing bacteria (BPF) at bio-slurry organic fertilizer. The acidity (pH) was increased in cow manure and slurry and bio-slurry organicertilizer media, while the temperature increased in the treatment of cow manure, slurry, and bio-slurry organic fertilizer.   Key words: phosphate solubilizing bacteria, cow manure, slurry, bio-slurry